Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a: \(=x^2-9-x^2+6x-9=6x-18\)
b: \(=x^3+x^2-x-1-x^3+27\)
\(=x^2-x+26\)
a: \(2x\left(x^2-3x+1\right)=2x^3-6x^2+2x\)
b: \(\left(x+2\right)^2-x^2=4x+4\)
c: \(\left(x+3\right)\left(x^2-3x+9\right)-x^3=27\)
2)a)3x(x-5)-(x-1)(2+3x)=30
<=>3x2-15x-3x2+x+2=30
<=>-14x+2=30
<=>-14x=30-2
<=>-14x=28
<=>x=-2
b)(x+2)(x+3)-(x-2)(x+5)=0
<=>x2+5x+6-x2-3x+10=0
<=>2x+16=0
<=>2x=-16
<=>x=-8
c)(3x+2)(2x+9)-(x+2)(6x+1)=9
<=>6x2+31x+18-6x2-13x-2=9
<=>18x+16=9
<=>18x=9-16
<=>18x=-7
<=>x=-7/18
câu d
\(D=\dfrac{\left(1-x^2\right)}{x}\left(\dfrac{x^2}{x+3}-1\right)+\dfrac{3x^2-14x+3}{x^2+3x}\)
\(\Leftrightarrow\left\{{}\begin{matrix}x\ne\left\{-3;0\right\}\\D=\dfrac{\left(1-x^2\right)\left(x^2-x-3\right)+3x^2-14x+3}{x\left(x+3\right)}\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x\ne\left\{-3;0\right\}\\D=\dfrac{x^2-x-3-x^4+x^3-3x^2+3x^2-14x+3}{x\left(x+3\right)}\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x\ne\left\{-3;0\right\}\\D=\dfrac{-x^4+x^3+x^2-15x}{x\left(x+3\right)}\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x\ne\left\{-3;0\right\}\\D=\dfrac{-x\left(x^3-x^2-x+15\right)}{x\left(x+3\right)}\end{matrix}\right.\)
\(\Leftrightarrow\left\{{}\begin{matrix}x\ne\left\{-3;0\right\}\\D=\dfrac{-\left(x^3-x^2-x+15\right)}{\left(x+3\right)}\end{matrix}\right.\)
a: \(=x^2-9-x^2+6x-9=6x-18\)
b: \(=x^3+x^2-x-1-x^3+27\)
\(=x^2-x+26\)